Approaches to Consider for Site-Specific Field Mapping: SL500/SS713, 8/2023 - Sharma, Lakesh K.; Ampatzidis, Yiannis (EDIS, 2023)
This publication discusses the general concept of site-specific farming, i.e., dividing a farm into several smaller management parcels instead of considering the whole farm as a single unit. This publication provides information on methods available that could be incorporated into the farming system for smart decision-making, for example, varying nutrient applications. The publication also discusses Normalized Difference Vegetative Index (NDVI) maps, Global Positioning System (GPS) units, yield monitors, and electrical conductivity maps.